Load Frequency Control using Classical controllers - Isemin, U. I.; Onah , A. J. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
This paper presents a solution to the problem of load frequency control of a two area power system using PI and PID controllers. In electric power systems, the load demand varies at different times of the day and these load variations lead to changes in frequency of the power system. In an interconnected power system, the tie-line power also varies in addition to the frequency variations. These changes in frequency and tie-line power causes instability in the power system network and make it unreliable. Load frequency control therefore ensures that these changes in the tie-line power and frequency of the control areas are minimized with acceptable level of overshoot and settling time. The method used involves the modeling of the two area interconnected power system using Matlab/Simulink software, the PI and PID controllers were then tuned using the Ziegler-Nichols tuning rule and used to simulate the two area power system when a load change of 0.2pu occurred in control area one. The simulation results showed that both the PI and PID controllers were able to restore the changes in tie line power and frequency of the control areas caused by the change in load to their steady state values of zero but the PID controller has better dynamic performances of overshoot, rise time and settling time than the PI controller.